Assessment of willingness to pay for drinking water quality improvement and supply services among households in Damaturu, Nigeria - Alhaji Dauda, Suleiman (2013)
Water is a fundamental need; all ecosystems including human being depend largely on availability of water, both in high quality and sustainable supply. Improved quality drinking water has the ability to improve our standard of living, reduces mortality rates and morbidity associated with water borne diseases. Damaturu have witnessed unprecedented increase in population due to its new status when made the capital of Yobe State in 1991. Provision of safe drinking water thus, became inadequate and a matter of serious concern, this led to prevalence of water borne diseases like diarrhea and other gastro intestinal disorder. Yobe State has embarked on the construction of “Yobe regional water supply project” which promises 100% access to portable water to Damaturu. The general objective of the study is to determine households’ willingness to pay for an improved quality drinking water. Choice experiment approach was used, and four attributes of drinking water quality were identified namely; tap water quality (TWQ), Tap water supply (TWS) tap water pressure (TWP) and Price. Random sample of 300 respondents were surveyed in- person. Conditional logit model (CLM), mixed logit model (MLM) and latent class logit model (LCM) were analyzed and interpreted. Discussion was made on the estimates obtained from the three models to find out households’ marginal willingness to pay and to assess household demand preferences on heterogeneous tap water attributes. TWQ3 is the most consistently valued among other attributes, in simple and interaction CLM mean WTP stood at 220% and 126%. While, in simple and interaction MLM mean WTP stood at 682% and 572%, but the mean WTP for LCM class1 and 2 unconditional stood at 190% and 126% conditional LCM for class1 and 2 is 152% and 120% respectively. TWS and TWP were equally valued.Respondents with higher level of education indicate high willingness to pay. Identifying the mix of attributes and their prices based on respondents’ drinking water demand preferences, would help policy makers to know and provides households with a preferred and affordable drinking water which would, facilitates effective tariff structure for cost recovery and sustainability.